2002
DOI: 10.1179/003258902225007005
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on dynamic compaction of metal powders: Part 1: Experimental

Abstract: used explosively powered projectiles to compact diVerent powdered materials. 4 -6 Petro Forge machines and similar This paper investigates the use of a simple drop weight equipments were also used for dynamic compaction process. 7 ,8 instrumented impact loading facility to produce metal Explosive isodynamic compaction also called direct powder compacts with better qualities than attained explosive compaction, is another type of dynamic comby the conventional means. Experiments were perpaction process. The powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A number of investigations of the High Velocity Compaction (HVC) process have been published in recent years [1][2][3][4][5]. All publications indicate that high-density components can be obtained using HVC.…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigations of the High Velocity Compaction (HVC) process have been published in recent years [1][2][3][4][5]. All publications indicate that high-density components can be obtained using HVC.…”
Section: Introductionmentioning
confidence: 99%
“…The main difference is the speed of the punches during compaction; see e.g. [1][2][3][4][5]. Green body cracks are primarily formed during compaction and ejection.…”
Section: Introductionmentioning
confidence: 99%
“…Hence in this present study, nitrogen atmosphere has been selected as the sintering protective atmosphere. [1] D. Roshan Kumar et al carried out experiments on dynamic compacting and quasistatic compacting of Fe, Fe-C-Cu-Mn powder and Cu-Zn powder and they have reported that densification and dimensional accuracy is better in dynamic compaction than quasistatic compaction. [2] D. Korachkin et al investigated the tensile failure of Distaloy AE ferrous powder and Alumina powder using three point bending test and diametral compression test and they have reported that ferrous powder showed a nonlinear increase in powder strength at higher density level whereas Alumina powder showed a linear increase in tensile strength.…”
Section: Introductionmentioning
confidence: 99%